Enhancing iron content and growth of cucumber seedlings with MgFe-LDHs under low-temperature stress - Hongyang Wu; Xiaoyang Wan; Jiefei Niu; Yidan Cao; Shufang Wang; Yu Zhang; Yayu Guo; Huimin Xu; Xian Xue; Jun Yao; Cuifang Zhu; Yang Li; et al. (Journal of Nanobiotechnology, 2024)
Abstract The development of cost-effective and eco-friendly fertilizers is crucial for enhancing iron (Fe) uptake in crops and can help alleviate dietary Fe deficiencies, especially in populations with limited access to meat. This study focused on the application of MgFe-layered double hydroxide nanoparticles (MgFe-LDHs) as a potential solution. We successfully synthesized and characterized MgFe-LDHs and observed that 1–10 mg/L MgFe-LDHs improved cucumber seed germination and water uptake. Notably, the application of 10 mg/L MgFe-LDHs to roots significantly increased the seedling emergence rate and growth under low-temperature stress. The application of 10 mg/L MgFe-LDHs during sowing increased the root length, lateral root number, root fresh weight, aboveground fresh weight, and hypocotyl length under low-temperature stress. A comprehensive analysis integrating plant physiology, nutrition, and transcriptomics suggested that MgFe-LDHs improve cold tolerance by upregulating SA to stimulate CsFAD3 expression, elevating GA3 levels for enhanced nitrogen metabolism and protein synthesis, and reducing levels of ABA and JA to support seedling emergence rate and growth, along with increasing the expression and activity of peroxidase genes. SEM and FTIR further confirmed the adsorption of MgFe-LDHs onto the root hairs in the mature zone of the root apex. Remarkably, MgFe-LDHs application led to a 46% increase (p < 0.05) in the Fe content within cucumber seedlings, a phenomenon not observed with comparable iron salt solutions, suggesting that the nanocrystalline nature of MgFe-LDHs enhances their absorption efficiency in plants. Additionally, MgFe-LDHs significantly increased the nitrogen (N) content of the seedlings by 12% (p < 0.05), promoting nitrogen fixation in the cucumber seedlings. These results pave the way for the development and use of LDH-based Fe fertilizers. Graphical Abstract